Effect of compaction of soils on growth of Acacia mangium Willd. under glasshouse conditions - Jusoff, K. (Kluwer Academic Publishers, 1991)
A glasshouse study was conducted to observe the initial height and diameter growth of Acacia mangium Willd, seedlings over a period of 24 weeks in pots with soil at bulk densities of 0.8, 1.0, 1.2, 1.4, 1.6, 1.8 and 2.0 g/cm3. Height and diameter growth increased significantly with decreasing soil bulk density. Significant differences in seedling diameter appeared during the tenth to twelfth week after transplanting and continued to increase until harvesting at week 24. The interaction between site water stress and compaction is discussed. A better understanding of these processes and the influence of site/soil factors on them is essential to the development of effective stand manipulation programs.